Peran Pesantren dalam Meningkatkan Pendidikan Islam di Indonesia - Azhar, Dzul; Anshory, Isa (Lembaga Yasin AlSys, 2024)
The purpose of this discussion is to determine the role of Islamic boarding schools in education in Indonesia. This discussion uses a qualitative approach and literature study methods. The aim of Islamic boarding school education is to develop an Islamic personality, namely a personality who has faith and is devoted to allah SWT. Have noble character, be useful and serve the people (khadim al ummah). Islamic boarding school heve long been institutions that have made an important contribution in participating in educating the nation. Islamic boarding school are not only religious institutions. Islamic boarding schools also act as educational, scientific, training, community development institutions, bases for colonial resistance and at the same time as cultural nedes.